2013
DOI: 10.3109/2000656x.2013.834612
|View full text |Cite
|
Sign up to set email alerts
|

Revision of a failed Swanson arthroplasty to a total wrist replacement restores wrist function and movements

Abstract: This study reports a case of revision of a failed Swanson silastic interpositional wrist replacement to a Universal 2 (KMI Medical Inc., San Diego, CA, Jan 2009) total wrist arthroplasty, in a 68-year-old woman with rheumatoid arthritis and pyrophosphate arthropathy. At the 2-year follow-up, the patient was pain-free and was able to perform all activities of daily living, documented by subjective assessment and objective scores. The disabilities of the arm, shoulder, and hand (DASH) scores improved from 98.3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is difficult to compare the 82% 5-year survival rate with previous studies as published data are limited to two case reports. 18,19 The previous reporting of clinical outcomes is variable. Two studies identified that the Biaxial implant achieves 19 degrees of mean flexion and 31 and 36 degrees of mean extension when used as a revision prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare the 82% 5-year survival rate with previous studies as published data are limited to two case reports. 18,19 The previous reporting of clinical outcomes is variable. Two studies identified that the Biaxial implant achieves 19 degrees of mean flexion and 31 and 36 degrees of mean extension when used as a revision prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies reviewed the revision of a failed TWA by replacing the implant with a different type (Cobb and Beckbaugh, 1996; Fatti et al., 1991; Khan et al., 2014; Lorei et al., 1997; Pinder et al., 2018; Rettig and Beckenbaugh, 1993). These studies concerned small and/or heterogeneous case series or case reports and described short-term, sometimes mid-term, outcomes.…”
Section: Introductionmentioning
confidence: 99%